Experimental Autoimmune Encephalomyelitis Development Is Aggravated by Candida albicans Infection - Fraga-Silva, Thais F. C. [UNESP]; Mimura, Luiza A. N. [UNESP]; Marchetti, Camila M. [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Franca, Thais G. D. [UNESP]; Zorzella-Pezavento, Sofia F. G. [UNESP]; Venturini, James [UNESP]; Arruda, Maria S. P. [UNESP]; Sartori, Alexandrina [UNESP] (Hindawi Publishing Corporation, 2015)
Multiple sclerosis (MS) is an inflammatory/autoimmune disease of the central nervous system (CNS) mainly mediated by myelin specific T cells. It is widely believed that environmental factors, including fungal infections, contribute to disease induction or evolution. Even though Candida infection among MS patients has been described, the participation of this fungus in this pathology is not clear. The purpose of this work was to evaluate the effect of a Candida albicans infection on experimental autoimmune encephalomyelitis (EAE) that is a widely accepted model to study MS. Female C57BL/6 mice were infected with C. albicans and 3 days later, animals were submitted to EAE induction by immunization with myelin oligodendrocyte glycoprotein. Previous infection increased the clinical score and also the body weight loss. EAE aggravation was associated with expansion of peripheral CD4(+) T cells and production of high levels of TNF-alpha, IFN-gamma IL-6, and IL-17 by spleen and CNS cells. In addition to yeast and hyphae, fungus specific T cells were found in the CNS. These findings suggest that C. albicans infection before EAE induction aggravates EAE, and possibly MS, mainly by CNS dissemination and local induction of encephalitogenic cytokines. Peripheral production of encephalitogenic cytokines could also contribute to disease aggravation.